2007
DOI: 10.1139/b07-019
|View full text |Cite
|
Sign up to set email alerts
|

Engineering nitrogen use efficiency with alanine aminotransferase

Abstract: Nitrogen (N) is the most important factor limiting crop productivity worldwide. The ability of plants to acquire N from applied fertilizers is one of the critical steps limiting the efficient use of nitrogen. To improve N use efficiency, genetically modified plants that overexpress alanine aminotransferase (AlaAT) were engineered by introducing a barley AlaAT cDNA driven by a canola root specific promoter (btg26). Compared with wild-type canola, transgenic plants had increased biomass and seed yield both in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
143
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(152 citation statements)
references
References 36 publications
4
143
0
5
Order By: Relevance
“…f r ) , i n G e r m a n y (PreBreedYield: Samans et al 2013), and in the UK (NUECrops: http://research.ncl.ac.uk/nefg/nuecrops/). Good et al (2007) demonstrated the promise of alternative breeding technologies in generating new diversity by improving the NUE of rapeseed through the overexpression of a barley alanine aminotransferase gene in the roots. N efficiency is also now gaining importance in the marketing of new rapeseed varieties.…”
Section: Resultsmentioning
confidence: 99%
“…f r ) , i n G e r m a n y (PreBreedYield: Samans et al 2013), and in the UK (NUECrops: http://research.ncl.ac.uk/nefg/nuecrops/). Good et al (2007) demonstrated the promise of alternative breeding technologies in generating new diversity by improving the NUE of rapeseed through the overexpression of a barley alanine aminotransferase gene in the roots. N efficiency is also now gaining importance in the marketing of new rapeseed varieties.…”
Section: Resultsmentioning
confidence: 99%
“…Improved N use efficiency (NUE) by overexpression of a barley alanine aminotransferase gene (AlaAT) in canola (Good et al 2004) and rice (Shrawat et al 2008) is notable as increased biomass and grain yield were recorded at low N supply (0.5-4 mM) in hydroponics, growth chambers and field conditions. However, several challenges exist in assessing this 'phenotype' in transgenic plants, viz.…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…In a collaboration with biotechnology company Monsanto in St Louis, Missouri, separate field studies 5 showed that the transgenic oilseed rape produced 42% more seeds under low-nitrogen conditions than did conventional controls. They also found that the GM crop needed 40% less nitrogen fertilizer to achieve yields equivalent to those of unmodified crops.…”
Section: "There Is a Huge Worldwide Potential For These Traits To Helmentioning
confidence: 99%